Developing an Islamic Accounting Information System Theory: Integrating Islamic Accounting Principles, Information Technology, and Maqashid al-Shariah Values in Financial Reporting Systems - Wali Saputra (Indo Publishing, 2026)
This study aims to develop a theory of the Islamic Accounting Information System (I-AIS) by explaining the integration of Islamic accounting principles, information technology, and the values of maqashid al-shariah within financial reporting systems. Using an exploratory qualitative approach through literature review and expert interviews, the study identifies three core components of I-AIS: the Islamic accounting pillar, the information technology pillar, and the Islamic ethical (sharia) pillar. The findings indicate that I-AIS functions not only as a tool for recording transactions but also as an instrument for strengthening accountability, transparency, and sharia compliance. The thematic analysis results in a conceptual model illustrating how Islamic accounting information systems can support financial management efficiency, sharia auditing processes, and reporting of Islamic social funds such as zakat and waqf. This research offers a theoretical contribution by expanding the scope of modern accounting information systems based on Islamic ethical values, as well as practical implications for policy development, education, and the digital Islamic finance industry.